Gamification enjoyment influences repurchase intention through emotional engagement in generation Zillennials - Indriastuti, Herning; Ramadhanti , Alfianty Rizky (Privietlab, 2025)
The demise of e-commerce marketplaces in Indonesia is due to the different strategies employed by companies. Two marketplaces in Indonesia still survive by using gamification strategies. Although this strategy does not always directly increase repurchase intention, this study aims to examine the repurchase intention of the Indonesian Zillennial generation on e-commerce platforms through gamification enjoyment and affective emotional engagement. This study used a purposive sampling technique to gather 130 responses for data analysis using SMARTPLS. Gamification has an insignificant effect on Zillennials' generation repurchase intention. However, affective emotional engagement can significantly increase the repurchase intention of the Zillennials generation and mediate the relationship between gamification enjoyment and the repurchase intention of the Zillennials generation. This is a valuable strategic input for e-commerce to keep in mind that the Zillennial generation's gaming experience always involves emotions (S-O-R Theory), and managing affective emotional engagement effectively will lead to more informed decisions, which is an unmapped territory in gamification marketing. The policy implication is that the high usage of social media and digital platforms through gamification enjoyment is expected to boost Zillennial consumer repurchase intentions through affective emotional engagement as an effective and accurate strategy to strengthen corporate branding with next-generation consumers in the digital landscape. This study focuses on Zillennials who use gamification for enjoyment on e-commerce platforms.